IMPLEMENTATION OF LINEAR CONGRUENT METHOD ALGORITHM IN ANIMAL INTRODUCTION EDUCATION GAME BASED AUGMENTED REALITY - Aang Abdul Kohar; Sugeng Supriyadi; Heru Budiyanto; Yulyanto Yulyanto (Balong International Journal of Design, 2019)
Abstract Today, recognizing kinds of animal for the children is generally done by using a media guide, a poster image. However, this media is still considered to have shortcomings. Children tend to quickly get bored and less interested in the learning patterns, due to lack of interactivity of existing learning media. So the conventional learning less attractive and optimal. This paper aimed to establish the animal recognition learning applications by applying Augemented reality technology based on Android. The research methodology used includes collecting data by interview and literature study, the development of systems using the RUP method that consists of four stages, namely inception, elaboration, construction and transition, as well as th problem solving algorithm using LCM (Linear Congruent Method). LCM algorithm implementations carried out the stage of construction to randomize the animals in the game that made the introduction. Thus, the results of this paper is a game featuring animals with 3D objects. based testing, game applications have been made able to introduce animals in early childhood. Keywords: Game, Android, Augmented Reality, Animal, Linear Congruent Algorithm Method.